Transient Effect of Acute Mental Stress on Corrected QT Interval among Healthy Male Students - Adhikari Manandhar, Seerina; Pramanik, Tapas; Amatya, Mrigendra; Silvanus, Vinutha (Journal of Institute of Medicine Nepal, 2022)
Introduction The time taken for depolarization and repolarization of the heart is represented by the QT interval. Psychological factors such as active mental stress may influence the action potentials developed in the heart and may alter QT interval of an individual. Therefore, our study was targeted to find the transient effect of acute mental stress on corrected QT interval among healthy male students. Methods An experimental study was conducted among 55 male first year undergraduates studying medical and dental courses in Nepal Medical College and Teaching Hospital (NMCTH). The study was executed in the Electrocardiography (ECG) lab of Department of Physiology of NMCTH from September 2022 – December 2022. ECG was obtained before and after the application of active/acute mental stress using standard mental arithmetic test (MAT) for 1 minute. Results In comparison to rest, a statistically decreased RR interval and heart rate (p<0.001) was observed after MAT. A statistically significant decrease in QT interval [0.35 ± 0.05/sec Vs 0.32± 0.05/sec] (p<0.001) and QTc interval [0.41± 0.05 /sec Vs 0.39± 0.05/sec] (p<0.001) was observed after MAT. Nevertheless, there was no statistically significant change in QRS duration [0.042 ± 0.009 per second at rest Vs 0.042 ± 0.009 per second] after the MAT (p=0.16). Conclusion Acute mental stress causes shortening of the QTc interval in young healthy males.